The Profile of Hospitalized Patients with Esophageal Cancer at Dr. Cipto Mangunkusumo General National Hospital in 2002-2008 - Bambang Sutopo; Dadang Makmun; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2009)
Background: Esophageal cancer is a rare but fatal disease. Neither data nor patterns of the disease have been published in Indonesia. Therefore, we aim to identify the profiles of patients with esophageal cancer who were hospitalized at Cipto Mangunkusumo hospital. The objective of our study was to recognize the prevalence of esophageal cancer, characteristics of the disease, diagnostic procedures and the treatment. Method: This was a retrospective study. The data was obtained from medical records of patients with esophageal cancer who were hospitalized at Cipto Mangunkusumo hospital from 2002 to 2008. Results: Twenty three patients, 13 males, were diagnoses with esophageal cancer during 2002–2008. All diagnoses were confirmed by histological examinations. Almost all patients were anemic at first presentation, but hipoalbuminemia were observed only in three patients. CT scan examination was more superior to chest X-ray and abdominal ultrasonography on detecting distant metastasis. Esophageal mass at 1/3 proximal of esophagus was found in four patients during endoscopic examination; while seven patients had esophageal mass located at 1/3 mid-portion of esophagus and 12 patients had esophageal mass located at 1/3 distal of the esophagus. Histological findings showed that 11 patients had adeno-carcinomas, eight patients had squamous cell carcinomas, three patients had squamous- adenocarcinomas and a patient was suspected to have sarcoma. Therapeutic measures had been done for 10 patients including gastrostomia in six patients, gastroesophageal resection in two patients and two patients received chemotherapy. Conclusion: We found that adenocarcinomas is more common than squamous-cell carcinomas among patients with esophageal cancer. Almost all esophageal cancer patients came to the hospital in late stage. Keywords: esophageal cancer, adenocarcinomas, squamous-cell carcinomas, squamous- adenocarcinomas, sarcomas